Estudo sobre a tensão de aderência em concretos autoadensáveis com baixo consumo de cimento reforçado com fibras de aço - Storch, Izabella Sant'Ana (2023)
This research studied the behavior of Self-Compacting Concrete with Low Cement Consumption (SCCLCC) with steel fibers reinforced in their properties in both states fresh and hardened, related to mechanical properties including bond strength. Variable concrets were produced, such as, reference concretes and concretes with the variation of two levels of reduction of cement consumption (12.5% and 17.5%), two levels of reinforcement with steel fiber (0.5% and 0.8%), and, finally, two diameters of steel bar for the pullout tests (10 mm and 16 mm). The results were compared with the values obtained by formulations found in the technical literature and normative codes, which underestimated the values obtained experimentally, in most cases. Equations were proposed for predicting bond strength using regression models. It has been demonstrated that it is possible to produce SCCLCC with steel fibers reinforced maintaining the properties in the fresh state (spreading test) and its mechanical performance. The equations for predicting the ultimate bonding strength (τu), τ1,0, and the bonding strength curve vs. slip (τδ) showed a high degree of accuracy with the experimental results.